Multi‐exon COL5A1 deletion in a child with classical Ehlers–Danlos syndrome: A case report expanding the allelic spectrum and showing evidence of parental gonosomal mosaicism. Issue 10 (11th October 2022) - Strang‐Karlsson, Sonja; Keigwin, Sylvia; Anttonen, Anna‐Kaisa; Baker, Duncan; Bean, Kerry; Jakkula, Eveliina
Abstract: Classical Ehlers–Danlos syndrome (cEDS) is a rare inherited autosomal dominant connective tissue disorder with core clinical features including skin hyperextensibility, abnormal scarring, and generalized joint hypermobility. Classical EDS is predominantly caused by small pathogenic variants in the genes COL5A1 and COL5A2 and occasionally by a COL1A1 point mutation p.(Arg312Cys), while gross deletions or duplications are uncommon. Gonosomal mosaicism is thought to be exceedingly rare with only two cases reported in the literature. We report a child with cEDS due to a rare gross deletion of exons 2–65 in the COL5A1 gene, inherited from an unaffected mosaic father. The level of mosaicism in the father was approximately 43% in leucocyte cells and 30% in DNA extracted from skin. Our results expand the allelic spectrum of cEDS variants and suggest that parental mosaicism needs to be considered in patients with suspected cEDS, given its implication for genetic counseling. Abstract : Classical Ehlers–Danlos syndrome is typically caused by point mutations and small insertion/deletions. We report a case of a large multi‐exon deletion, inherited from an unaffected father who was mosaic for the deletion, with a relatively high level of mosaicism. Gonosomal mosaicism should be considered when discussing recurrence risks in families.